Efektivitas Penggunaan Buku Saku Terhadap Peningkatan Pengetahuan Ibu Hamil Tentang Pencegahan Stunting Di Desa Blang Krueng Kecamatan Baitussalam - Indri Silviana; Kiki Asrifa Dinen; Pasyamei Rembune Kala (Hikamatzu | Journal of Multidisciplinary, 2025)
Stunting is one of the major public health problems that remains highly prevalent in Indonesia, particularly in Aceh Province. This condition can be prevented early during pregnancy through appropriate education for pregnant women, one of which is by using pocket books as an educational medium. This study aimed to determine the effectiveness of using pocket books in improving pregnant women's knowledge regarding stunting prevention in Blang Krueng Village, Baitussalam District. The research question in this study is: How effective is the use of pocket books in increasing pregnant women's knowledge about stunting prevention in Blang Krueng Village. This study employed a pre-experimental design with a one-group pretest-posttest approach. The population in this study consisted of all pregnant women in Blang Krueng Village, Baitussalam District, totaling 20 individuals. The sampling technique used was total sampling, where the entire population served as the sample. Data collection was conducted using a questionnaire administered before and after the intervention. Data analysis was performed using the paired sample t-test. The results showed a significant increase in knowledge after the use of the pocket book, with a mean pretest score of 10.15 and a mean posttest score of 17.70, indicating that all respondents experienced an improvement from moderate and low knowledge categories to good. The conclusion of this study is that pocket books are effective educational media for improving pregnant women's knowledge of stunting prevention. The researcher suggests that pocket books be widely implemented in educational programs at community health centers (posyandu) or other health services as part of preventive interventions against stunting, and should be tailored to local characteristics to enhance understanding.